Quality of Sibling Relationships in Maltreated Youth Residing in Out-of-Home-Care - Milojevich, Helen M. (Journal of interpersonal violence, 2021)
When children are removed from their parents’s custody because of substantiated maltreatment and placed in out-of-home placements, they may be placed separately from siblings, potentially leading to even higher levels of stress in children. This possibility emerges insofar as siblings serve as a source of support during the uncertain times that accompany maltreatment and subsequent removal. We explored these issues in the present study, focusing on whether sibling relationship quality was related to post-removal behavioral functioning in maltreated children and adolescents. A total of 102 six- to seventeen-year-olds residing in a residential facility completed questionnaires about their sibling relationship quality and behavioral functioning. With age, sibling relationships became more hostile; although in girls, sibling affection also increased with age, at least when their sibling was a girl. Sibling hostility was related to increases in aggression and behavioral problems. Surprisingly, greater sibling affection was associated with increased problems, particularly when children had little contact with their sibling. Results provide insight into perceptions of sibling relationships in maltreated children and have implications for placement decisions.